2016
DOI: 10.1016/j.jenvrad.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Natural and anthropogenic radionuclide activity concentrations in the New Zealand diet

Abstract: To support New Zealand's food safety monitoring regime, a survey was undertaken to establish radionuclide activity concentrations across the New Zealand diet. This survey was undertaken to better understand the radioactivity content of the modern diet and also to assess the suitability of the current use of milk as a sentinel for dietary radionuclide trends. Thirteen radionuclides were analysed in 40 common food commodities, including animal products, fruits, vegetables, cereal grains and seafood. Activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The highest activity concentrations of 210 Po have been reported in mushrooms from Scandinavia [23,59,60] and in mushrooms growing close to a uranium mine in Germany [61], while the lowest levels are seen in collections from Poland and New Zealand [57,[62][63][64][65][66] (Table 1). The authors Guillén and Baeza (2014) noted that the pattern distribution of 210 Po seemed to be species-dependent [67], but a comparison of inter-genus data shows that the most important aspects are local conditions, e.g., natural radioactivity, atmospheric fallout, geological conditions, etc.…”
Section: Naturally Occurring Radioisotopes In Mushroomsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest activity concentrations of 210 Po have been reported in mushrooms from Scandinavia [23,59,60] and in mushrooms growing close to a uranium mine in Germany [61], while the lowest levels are seen in collections from Poland and New Zealand [57,[62][63][64][65][66] (Table 1). The authors Guillén and Baeza (2014) noted that the pattern distribution of 210 Po seemed to be species-dependent [67], but a comparison of inter-genus data shows that the most important aspects are local conditions, e.g., natural radioactivity, atmospheric fallout, geological conditions, etc.…”
Section: Naturally Occurring Radioisotopes In Mushroomsmentioning
confidence: 99%
“…In the case of thorium, the highest activity concentrations of 228 Th and 232 Th have been noticed in Brazil, with the lowest in Poland [73,76,78,[83][84][85][86][87][88][89][90][91]. In the case of uranium, the highest activity concentrations of the alpha emitters 234 U, 235 U and 238 U have been reported in mushrooms from Germany, Turkey, Finland, and Slovakia [60,61,86,88,90], with the lowest being in Poland, Serbia, Bosnia and Herzegovina as well as China (Yunnan) and New Zealand [58,62,70,71,78,83,84,89,[91][92][93][94][95]. If the uranium activity is compared to its daughter nuclide, 226 Ra, the maximum radium activity concentration is always higher than the activity of the parent ( 238 U).…”
Section: Naturally Occurring Radioisotopes In Mushroomsmentioning
confidence: 99%
“…Previous studies revealed that 210 Po was an important contributor to human ionizing radiation exposure through food [ 11 ]. A study on establishing radionuclide activity concentrations in a New Zealand diet revealed the determination of 210-Po activity in 103 of 160 analyzed samples that encompassed a large variety of the foods [ 16 ]. The research of Meli et al [ 17 ] revealed that an effective dose from 210 Po ingested by the total diet accounts for 5–12% of the natural radiation exposure in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring radionuclides such as 232 Th, 238 U and 40 K present in foodstuffs have significant effects on the human health when taken in very high quantity (Pearson et al 2016). Oral consumption of 238 U for instance, can lead to high chances of the lung cancer and damage of the kidney cells (Abojassim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%